Soft Skill Sebagai Upaya Peningkatan Kualitas Layanan Satu Pintu di Kota Semarang - Widiastuti, Tantri; Aditya, Elma Muncar; Paranita, Ekayana Sangkasari (Jurnal Aplikasi Manajemen, 2014)
The purpose of this research is to increasing the service quality of (BPPT) Kota Semarang staffs by optimizing their soft skills. This research is comparing the service quality of BPPT Kota Semarang staffs before and after training. The result of this research showed that the given soft skill training was only able to contribute positively on permit applicant's satisfaction of four instruments. The four instruments were complaint, staff politeness and hospitality, and staff speed and responsiveness in giving service. However, of the four instruments that were related to human resource were staff politeness and hospitality and staff speed and responsiveness in giving service while the adjustment of paid fee and fixed fee and complaint facility influenced by the system.